2014
DOI: 10.1186/s13023-014-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlation in Pompe disease, a step forward

Abstract: BackgroundPompe’s disease is a progressive myopathy caused by mutations in the lysosomal enzyme acid alphaglucosidase gene (GAA). A wide clinical variability occurs also in patients sharing the same GAA mutations, even within the same family.MethodsFor a large series of GSDII patients we collected some clinical data as age of onset of the disease, presence or absence of muscular pain, Walton score, 6-Minute Walking Test, Vital Capacity, and Creatine Kinase. DNA was extracted and tested for GAA mutations and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 54 publications
3
52
1
1
Order By: Relevance
“…In a larger cohort of Pompe patients (N = 85), individuals with the D/D ACE genotype presented with an earlier onset of disease and muscle pain, confirming the previous observation [7]. The relationship between ACE genotype and clinical parameters in a cohort of LOPD patients who received biweekly infusions of alglucosidase alfa for N 2 years also was reported [14].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In a larger cohort of Pompe patients (N = 85), individuals with the D/D ACE genotype presented with an earlier onset of disease and muscle pain, confirming the previous observation [7]. The relationship between ACE genotype and clinical parameters in a cohort of LOPD patients who received biweekly infusions of alglucosidase alfa for N 2 years also was reported [14].…”
Section: Introductionsupporting
confidence: 71%
“…We also demonstrated the presence of this association regardless of baseline disease severity and anti-GAA IgG antibody levels. However, unlike patients in earlier studies [7,13], LOTS patients with the D/D genotype did not present with an earlier onset of disease or a longer duration of disease at study entry.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…11 out of 17 patients with known genotype carry the c.-32-13TN G mutation. The correlation between genotype and phenotype is most likely blurred by being a small cohort and other modifying factors described previously [36,37,38]. Kroos et al [38] reported that the presence of at least one mutation allows the production of a protein with some residual activity that leads to the late-onset forms.…”
Section: Discussionmentioning
confidence: 99%
“…A European newborn screening study showed that the carrier frequency of c.-32-13T > G in the European general population is 1 in 154; the exon 18 deletion, 1 in 187; and c.525delT, 1 in 284 [28]. Currently, > 400 pathogenic variants have been reported in the GAA gene (http://cluster15.erasmusmc.nl/klgn/pompe/mutations.html?lang=en accessed May 22, 2017) [29,30]. The c.-32-13T > G variant, seen in 68–90% of Caucasian patients with LOPD in a heterozygous or homozygous state [3136], results in alternatively spliced transcripts with deletion of exon 2 and leakage of some normal transcripts [32,37].…”
Section: Introductionmentioning
confidence: 99%